Ecological design - Lundbladh, Karolina (2007)
It has become increasingly clear that the actions of humans are affecting the biosphere in a dramatic way. By using too much fossil fuel and chemicals that pollutes air, water and land, by devastating large areas of forest, homogenizing large tracks of land through agriculture and by fishing the seas dry, humans cause global warming and the extinction of millions of plant and animal species. At the same time there is an unprecedented awareness of environmental issues, and many people are willing to change their lifestyle in order to contribute to a more sustainable society.